Cultural Politics and Communication Strategies in Pesantren Adaptation to Modernity: A Case Study of Pesantren Tebuireng - Arianto, Nanang; Nasution, Ridwan; Singarimbun, Junedi; Hasibuan, Susanti (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study analyzes how Pesantren Tebuireng adapts to the demands of modernity through cultural politics and communication strategies, two concepts that have not been fully explained in the context of traditional Islamic educational institutions. Despite numerous studies on pesantren and their role in Islamic education, a research gap remains in understanding how pesantren maintain their authority amidst globalization and changing state policies. To fill this gap, this study aims to explain how pesantren, specifically Pesantren Tebuireng, can survive and adapt to the times through cultural politics and communication strategies. Using a qualitative approach with a case study design, this study collected data through observation, interviews, and documentation, and analyzed it using triangulation techniques to ensure credibility. The theoretical framework used is cultural politics and communication strategies, which are operationalized by examining how pesantren maintain tradition while responding to external regulations and managing their image in society. The main findings indicate that Pesantren Tebuireng successfully maintains its religious identity through selective adaptation to modernity, utilizing cultural politics to maintain institutional autonomy, and implementing communication strategies to build public trust. This research contributes to the discourse on pesantren adaptation by emphasizing how communication strategies and cultural politics can serve as tools for maintaining identity and power in the face of modernity. These findings enrich existing debates on the relationship between tradition, power, and communication in the context of religious institutions and open up further research directions that deepen the interaction between pesantren and broader socio-political dynamics.